2020
DOI: 10.21203/rs.3.rs-37608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 pandemic fear and anxiety among healthcare professionals in Pakistan

Abstract: During the current pandemic, Pakistan is badly affected. It has exerted great pressure on vigor as well as the psychology of the healthcare professionals. Limited resources, illiteracy, myths, and not following the proper protocol by the general population may have increased the risk for everyone, and anxiety and fear among the frontline healthcare professionals. Anxiety is a common response to any stressful situation and its the fear of the unknown and it may have multiple consequences.In the current study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
3
28
0
6
Order By: Relevance
“…Further to the above, fears about contracting the COVID-19 disease and/ or infecting one's family members/ loved ones emerged as a major source of stress among healthcare staff. Even when the initial experience of psychological chaos was low with existing high standards of infection prevention strategies, fear of contracting the disease remained a signi cant concern among healthcare staff (43)(44)(45)(46)(47)(48)(49). Healthcare staff who contracted the disease were faced with additional fears of dying alone with feelings of being socially isolated from colleagues and family/ loved ones as they underwent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further to the above, fears about contracting the COVID-19 disease and/ or infecting one's family members/ loved ones emerged as a major source of stress among healthcare staff. Even when the initial experience of psychological chaos was low with existing high standards of infection prevention strategies, fear of contracting the disease remained a signi cant concern among healthcare staff (43)(44)(45)(46)(47)(48)(49). Healthcare staff who contracted the disease were faced with additional fears of dying alone with feelings of being socially isolated from colleagues and family/ loved ones as they underwent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that more than 50% of healthcare professionals report symptoms of depression, insomnia, and anxiety due to COVID-19 [35]. A recent study carried out in Pakistan on fear and anxiety among healthcare professionals reported that about three-fourth of them had fear of getting infected during the management of COVID-19 patients, and another two-third reported severe anxiety, which was particularly more common among nurses [36]. Studies also reported excessive workload, isolation, mental stress and discrimination among frontline health professionals, thus, contributing to physical exhaustion, emotional disturbance, worry and fear [37].…”
Section: Discussionmentioning
confidence: 99%
“…The scale has been tested for its reliability in different studies. It was reported that Cronbach's alpha of the FCV-19S was 0.82, and test-retest reliability (ICC) was 0.72 (Carre, Griffiths, & Mailliez, 2020;Martínez-Lorca, Martínez-Lorca, Criado-Álvarez, & Armesilla, 2020;Masjoudi, Aslani, Khazaeian, & Fathnezhad-Kazemi, 2020;Saleem et al, 2020).…”
Section: Tool Ii: the Fear Of Covid-19 Scale (Fcv-19s)mentioning
confidence: 99%